ANALISIS PERILAKU PEMBELIAN IMPULSIF PADA KONSUMEN ONLINE DI PROVINSI JAMBI - Irfan Hassandi; Mardiana R; Hanan Laras Sabrina; Herry Mulyono; Felyx Marcelino (Jurnal Manajemen dan Bisnis Performa, 2024)
This research aims to find the variable that influences impulsive buying behavior for online customers in Jambi province. The model used for this research is Stimulus-organism-respond model. There are 2 independent variables, 2 mediating variables and 1 dependent variable interpret Stimulus-organism-respond model. To test the model this research used Structural Equation modelling. The result shows the variable that influences impulsive buying behavior of Jambi province buyers is arousal. SMEs in Jambi can develop more strategies to encourage the arousal of online customer such creating a periodical sales discount with the aim of the program to gain impulsive buying behavior from customer arousal and increasing sales from that behavior.